Topical vapocoolant spray reduces nociceptive response to ear notching in neonatal piglets. (May 2018) - Lomax, Sabrina; Hall, Evelyn; Oehlers, Lauren; White, Peter
Abstract: Objective: To evaluate the efficacy of a vapocoolant spray (VS) to provide local anaesthesia for piglets during ear notching. Study design: Randomized study. Animals: Eleven 10 day old and forty 3–5 day old Large White piglets. Methods: Temperature validation studies using thermocouples and a temperature data logger were conducted on dead and live tissue to determine optimal spray distance and duration to reduce tissue temperature to below 10 °C. A behavioural trial was conducted to assess efficacy for ear notching. Piglets were randomly assigned to one of four treatment groups: positive control (POS; n  = 10), VS ( n  = 10), lignocaine (LIG; n  = 10) and negative control (NEG; n  = 10). Spray was administered to the margin of each ear, from a distance of 10 cm, and for a duration of 2 seconds immediately prior to ear notching. Behavioural observation was used to assess movement and vocal response, with responses categorized as no response (0) and response (1). Results: Temperature and tissue validation studies indicated that a 2 second spray from 10 cm reduced tissue temperature to below 10 °C, and reduced response to stimulation of the skin with an 18 gauge needle ( p < 0.001). There was a significant effect of treatment on response to ear notching ( p < 0.001). The probability of a piglet to respond to ear notching was 98.7% for NEG piglets, compared with those treated with VS (5.3%), LIG (1.1%) and sham-notched piglets (0.9%). Conclusions and clinical relevance: This study contributes new data on the pain of ear notching in piglets. The application of a topical VS prior to ear notching reduced the antinociceptive response of piglets to the procedure, similar to that of a local anaesthetic. Cryoanaesthesia presents a simple and effective option for reducing the pain response to this simple husbandry procedure.